Biosorption characteristic of Alcaligenes sp. BAPb.1 for removal of lead(II) from aqueous solution - Jin, Yu (3 Biotech, 2017)
In this study, strain BAPb.1 was isolated from lead mining area and used as an adsorbent to remove lead(II) ions from aqueous solution. The physicochemical characteristics, heavy metal resistance and antibiotic sensitivity of strain BAPb.1 were investigated. Biosorption capacity was evaluated by batch biosorption experiments, and isothermal characteristics were discussed. Atomic force microscopy (AFM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and Fourier transform infrared spectrometry (FTIR) were conducted to explore the mechanism for lead(II) adsorption. Based on morphological and physiological characteristics as well as the phylogenetic analysis of 16S rDNA sequences, strain BAPb.1 was identified as a member of the genus Alcaligenes. It exhibited high resistances to multiple heavy metals such as lead(II), copper(II), zinc(II), nickel(II) and chromium(VI), and to antibiotics such as kanamycin, ampicillin, streptomycin, chloramphenicol, and tetracycline. The optimum conditions for maximum biosorption rate of 85.2% and maximum capacity of 56.8 mg g(−1) were found at pH of 5, adsorbent dosage of 1.5 g L(−1) (dry weight), initial lead(II) concentration of 100 mg L(−1), and contact time of 30 min at 30 °C. Biosorption isotherms were well fitted with Langmuir isotherm model. Mechanism analysis reveals that the lead(II) ions may exchange with sodium and potassium ions, and the hydroxyl, carbonyl and phosphate groups on the cell surface can chelate the lead(II) ions, therefore, surface adsorption play significant role in the biosorption process.